Non convulsive refractory status epilepticus induced by thiocolchicoside (TCC) intrathecal injection: A case report. Issue 7 (8th February 2022) - Evangelista, Giacomo; Dono, Fedele; Consoli, Stefano; Pozzilli, Valeria; Calisi, Dario; Russo, Mirella; D'Orazio, Claudia; D'Andreagiovanni, Anna; Montesano, Giovanna; Rapini, Sabina; Caulo, Massimo; Onofrj, Marco; et al.
Abstract : TCC is a semisynthetic molecule widely used in clinical settings as a pain killer and myorelaxant. Several neurological side effects have been reported in association with TCC treatment including somnolence, confusion and seizure, the latter in a lower percentage of patients. Some previous reports described seizure onset after TCC intake in adulthood. However, major epileptological complication, namely status epilepticus, has never been previously reported in association with TCC treatment. In our report, we describe a case of acute refractory non‐convulsive status epilepticus (NCSE) in the context of a TCC‐induced acute toxic encephalopathy (ATE) in a woman without any previous neurological or physical comorbidities.